Container

A tapered container design for PTFE minimizes compaction and fibrillation, enabling stable storage and use as a binder for electrochemical devices at room temperature.

JP2025010033APending Publication Date: 2025-01-20DAIKIN INDUSTRIES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024105144
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-28
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Fibrillation of polytetrafluoroethylene (PTFE) occurs during storage and transportation, which is problematic when used as a binder for electrochemical devices due to the significant impact it has on the performance of these devices despite the small amount used.

Method used

A container with a cylindrical inner wall featuring a forward or reverse taper is designed to minimize the compaction of PTFE, thereby reducing fibrillation by minimizing the force applied by the PTFE's own weight, and is filled with PTFE to a mass of 10 kg or less, with optional use of a moisture absorbent to maintain a dry state.

Benefits of technology

The container effectively suppresses fibrillation of PTFE, allowing it to be stored at room temperature without temperature control, enhancing the handling and performance of PTFE as a binder for electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010033000001_ABST
    Figure 2025010033000001_ABST
Patent Text Reader

Abstract

To provide a container that is designed to prevent the fibrillation of polytetrafluoroethylene.SOLUTION: A container for filling polytetrafluoroethylene is cylindrical with a forward or inverse tapered inner side wall.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a container for filling with polytetrafluoroethylene. [Background technology]

[0002] Patent Documents 1 and 2 describe the use of an aqueous dispersion of polytetrafluoroethylene as a binder for batteries. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-31179 A [Patent Document 2] Japanese Patent Application Publication No. 11-343317 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a container in which fibrillation of polytetrafluoroethylene is unlikely to occur. [Means for solving the problem]

[0005] The present disclosure (1) is a container for filling polytetrafluoroethylene, the container having a cylindrical inner side wall with a forward or reverse taper.

[0006] The present disclosure (2) is the container according to the present disclosure (1), wherein the polytetrafluoroethylene has an extrusion pressure of 5 MPa or more at a reduction ratio of 100 and / or is stretchable.

[0007] The present disclosure (3) is the container according to the present disclosure (1) or (2), wherein the polytetrafluoroethylene has an extrusion pressure of 5 MPa or more at a reduction ratio of 100 and is stretchable.

[0008] The present disclosure (4) is the container according to any one of the present disclosures (1) to (3), wherein the extrusion pressure of the polytetrafluoroethylene at a reduction ratio of 100 is 5 to 20 MPa.

[0009] The present disclosure (5) is the container according to any one of the present disclosures (1) to (4), wherein the polytetrafluoroethylene is used as a binder for an electrochemical device.

[0010] The present disclosure (6) is the container according to any one of the present disclosures (1) to (5), in which the difference between the upper inner diameter and the lower inner diameter is 5 to 100 mm.

[0011] The present disclosure (7) is the container according to any one of the present disclosures (1) to (6), in which the taper angle is 0.5 to 10°.

[0012] The present disclosure (8) is the container according to any one of the present disclosures (1) to (7), wherein the material is polypropylene substantially free of plasticizer.

[0013] The present disclosure (9) is the container according to any one of the present disclosures (1) to (8), wherein the surface roughness of the inner wall is 1.00 μm or less.

[0014] The present disclosure (10) is a container according to any one of the present disclosures (1) to (9), comprising a body having an opening, a lid attached to the opening, and a clamp for fixing the lid.

[0015] The present disclosure (11) is the container according to the present disclosure (10), wherein the lid is attached to the opening in a state in which a step on the lid engages with a protrusion on the body and / or a protrusion on the lid engages with a step on the body.

[0016] The present disclosure (12) is the container according to any one of the present disclosures (1) to (11), wherein the polytetrafluoroethylene has a water content of 0.050% by mass or less.

[0017] The present disclosure (13) is the container according to any one of the present disclosures (1) to (12), wherein the polytetrafluoroethylene has an apparent density of 0.40 to 0.60 g / ml.

[0018] The present disclosure (14) is the container according to any one of the present disclosures (1) to (13), wherein the polytetrafluoroethylene has an apparent density of 0.43 to 0.60 g / ml.

[0019] The present disclosure (15) is the container according to any one of the present disclosures (1) to (14), wherein the polytetrafluoroethylene has a powder particle size of 300 to 700 μm.

[0020] The present disclosure (16) is the container according to any one of the present disclosures (1) to (15), wherein the polytetrafluoroethylene has a powder particle size of 500 to 700 μm.

[0021] The present disclosure (17) is the container according to any one of the present disclosures (1) to (16), wherein the standard specific gravity of the polytetrafluoroethylene is 2.200 or less.

[0022] The present disclosure (18) is the container according to any one of the present disclosures (1) to (17), wherein the standard specific gravity of the polytetrafluoroethylene is 2.130 to 2.170.

[0023] The present disclosure (19) is the container according to any one of the present disclosures (1) to (18), wherein the polytetrafluoroethylene has an apparent density of 0.43 to 0.60 g / ml, a powder particle size of 500 to 700 μm, and a standard specific gravity of 2.130 to 2.170.

[0024] The present disclosure (20) is the container according to any one of the present disclosures (1) to (19), wherein the polytetrafluoroethylene is a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing polymerization units based on tetrafluoroethylene and polymerization units based on a modified monomer.

[0025] The present disclosure (21) is the container according to the present disclosure (20), wherein the modifying monomer is at least one selected from the group consisting of perfluoro(methyl vinyl ether) and hexafluoropropylene.

[0026] The present disclosure (22) is the container according to any one of the present disclosures (1) to (21) filled with the polytetrafluoroethylene.

[0027] The present disclosure (23) is the container according to any one of the present disclosures (1) to (22), wherein the container includes a moisture absorbent.

[0028] The present disclosure (24) is a method for storing polytetrafluoroethylene, comprising filling the container according to any one of the present disclosures (1) to (23) with the polytetrafluoroethylene and storing the same.

[0029] The present disclosure (25) is a container for filling with polytetrafluoroethylene, wherein the mass of the polytetrafluoroethylene to be filled is 10 kg or less.

[0030] The present disclosure (26) is the container according to the present disclosure (25), wherein the mass of the polytetrafluoroethylene filled therein is 5 kg or less.

[0031] The present disclosure (27) is the container according to the present disclosure (25) or (26), wherein the powder particle size of the polytetrafluoroethylene is 100 μm or more and less than 600 μm.

[0032] The present disclosure (28) is the container according to any one of the present disclosures (25) to (27), wherein the polytetrafluoroethylene has an apparent density of 0.35 to 0.48 g / ml.

[0033] The present disclosure (29) is the container according to any one of the present disclosures (25) to (28), wherein the polytetrafluoroethylene has a water content of 0.050% by mass or less.

[0034] The present disclosure (30) is the container according to any one of the present disclosures (25) to (29), wherein the polytetrafluoroethylene has a water content of 0.005% by mass or less.

[0035] The present disclosure (31) is the container according to any one of the present disclosures (25) to (30), wherein the standard specific gravity of the polytetrafluoroethylene is 2.130 to 2.170.

[0036] The present disclosure (32) is the container according to any one of the present disclosures (25) to (31), wherein the polytetrafluoroethylene has a moisture content of 0.005% by mass or less, an apparent density of 0.35 to 0.48 g / ml, a powder particle size of 100 μm or more and less than 600 μm, and a standard specific gravity of 2.130 to 2.170.

[0037] The present disclosure (33) is the container according to any one of the present disclosures (25) to (32), wherein the polytetrafluoroethylene has a powder particle size of 100 μm or more and less than 300 μm, and / or an apparent density of 0.35 g / ml or more and less than 0.40 g / ml.

[0038] The present disclosure (34) is the container according to any one of the present disclosures (25) to (33) filled with the polytetrafluoroethylene. Effect of the Invention

[0039] According to the present disclosure, a container in which polytetrafluoroethylene is less likely to fibrillate can be provided. [Brief description of the drawings]

[0040] [Figure 1] FIG. 1 is a schematic diagram showing an example of a container according to the present disclosure. [Diagram 2] FIG. 2 is a partially enlarged view of the container of FIG. [Diagram 3] 2 is a schematic diagram of a clamp provided on the container of FIG. 1. [Figure 4] FIG. 13 is a schematic diagram showing a modified example of the container of the present disclosure. [Diagram 5]FIG. 13 is a schematic diagram showing a modified example of the container of the present disclosure. [Figure 6] FIG. 13 is a partially enlarged view showing a modified example of the container of the present disclosure. [Figure 7] FIG. 13 is a schematic diagram showing a modified example of the container of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] The present inventors have studied polytetrafluoroethylene and found that polytetrafluoroethylene, which is useful as a binder for electrochemical devices such as batteries, tends to be more prone to fibrillation than normal polytetrafluoroethylene when stored or transported in a container. In applications where a large amount of polytetrafluoroethylene is used, partial fibrillation does not cause a major problem, but when used as a binder for electrochemical devices, the amount used is small and the impact of fibrillation is large, so it is strongly required to suppress fibrillation.

[0042] As a result of further investigations, the inventors found that fibrillation of the filled polytetrafluoroethylene can be suppressed if the inner wall of the side surface is a cylindrical container with a forward or reverse taper, and arrived at the first present disclosure. The inventors also found that fibrillation of the filled polytetrafluoroethylene can be suppressed by setting the mass of the polytetrafluoroethylene filled in the container to 10 kg or less, and arrived at the second present disclosure.

[0043] The present disclosure will now be described in detail.

[0044] A first aspect of the present disclosure is a container for filling with polytetrafluoroethylene, the container having a cylindrical inner side wall with a forward or reverse taper.

[0045] Polytetrafluoroethylene (PTFE) filled in a container becomes hard as the PTFE powder (particles) are crushed and compacted by its own weight. Normally, PTFE powder needs to be loosened before use, and it is thought that fibrillation occurs when loosening such hardened powder. In the first container of the present disclosure, the inner wall of the side is tapered or reversed, so that the force generated by the weight is not easily applied to the PTFE powder and it is not easily compacted, thereby suppressing fibrillation.

[0046] In the container of the first disclosure, the mass of the PTFE to be filled is preferably 30 kg or less, more preferably 20 kg or less, and even more preferably 15 kg or less. The lower limit is not particularly limited, but is usually 1 kg or more.

[0047] The upper limit of the internal volume of the container of the first present disclosure is preferably 150 L or less, more preferably 120 L or less, even more preferably 100 L or less, and even more preferably 80 L or less. The lower limit is not particularly limited, but is preferably 5 L or more, more preferably 10 L or more, and even more preferably 20 L.

[0048] An example of the container according to the first embodiment of the present disclosure will now be described with reference to the drawings.

[0049] As shown in FIG. 1, the container 1 comprises a body 2, a lid 3 and a clamp 4.

[0050] The main body 2 is a cylindrical member with a tapered inner wall 2a and outer wall 2b on the side, and is filled with PTFE from an opening 2c on the top surface. After filling with PTFE, a lid 3 is attached to the opening 2c of the main body 2 and fixed with a clamp 4, thereby sealing the inside of the main body 2.

[0051] The lid 3 is a circular member configured to cover the opening 2c and side surface of the main body 2. As shown in Fig. 2, a step-like difference 3a is provided on the inside of the lid 3 where it contacts the outer wall 2b, and a protrusion 2d is provided on the outside of the opening 2c of the main body 2. The lid 3 is attached to the opening 2c with the step 3a and the protrusion 2d engaged. This improves the airtightness of the inside of the main body 2.

[0052] The clamp 4 is a ring-shaped member for fixing the lid 3 to the main body 2. As shown in Fig. 3, the clamp 4 is in an open state before attachment, and after attachment, the clamp 4 is closed and tightened by the attachment portion 4a to fix the lid 3 to the main body 2. This improves the airtightness of the inside of the main body 2.

[0053] PTFE used as a binder in electrochemical devices is required to have a low moisture content. The container 1 has an extremely high airtightness inside the main body 2 due to the above-mentioned configuration, so that the PTFE can be stored with a low moisture content.

[0054] The difference between the inner diameter of the upper surface and the inner diameter of the lower surface of the main body 2 is preferably 5 mm or more, more preferably 10 mm or more, even more preferably 15 mm or more, and particularly preferably 20 mm or more, and is preferably 100 mm or less, more preferably 80 mm or less, even more preferably 60 mm or less, and particularly preferably 50 mm or less. The upper surface inner diameter is preferably 250 mm or more, more preferably 300 mm or more, even more preferably 350 mm or more, and particularly preferably 400 mm or more, and is preferably 800 mm or less, more preferably 700 mm or less, and even more preferably 600 mm or less. The lower surface inner diameter is preferably 200 mm or more, more preferably 250 mm or more, even more preferably 300 mm or more, and particularly preferably 350 mm or more, and is preferably 750 mm or less, more preferably 650 mm or less, even more preferably 600 mm or less, and particularly preferably 550 mm or less.

[0055] The taper angle of the inner wall 2a is preferably 0.5° or more, more preferably 1° or more, even more preferably 1.5° or more, and particularly preferably 2° or more, and is preferably 10° or less, more preferably 9° or less, even more preferably 8° or less, even more preferably 7° or less, even more preferably 6° or less, and particularly preferably 5° or less. The suitable range of the taper angle of the outer wall 2b is the same as that of the inner wall 2a. The taper angle means the inclination angle of the wall surface with respect to the normal line (see "taper angle A" in FIG. 1).

[0056] The taper ratio of container 1 is preferably 0.01 or more, more preferably 0.02 or more, even more preferably 0.03 or more, even more preferably 0.04 or more, and particularly preferably 0.05 or more, and is preferably 0.20 or less, more preferably 0.19 or less, even more preferably 0.18 or less, even more preferably 0.17 or less, even more preferably 0.16 or less, and particularly preferably 0.15 or less. The taper ratio is a value defined by |inner diameter of upper surface of main body 2-inner diameter of lower surface of main body 2| / height of main body 2.

[0057] The height of the main body 2 is preferably 200 mm or more, more preferably 250 mm or more, and even more preferably 300 mm or more, and is preferably 500 mm or less, more preferably 450 mm or less, and even more preferably 400 mm or less.

[0058] The material of the container 1 (particularly the body 2 and the lid 3 that come into contact with PTFE) is preferably polypropylene that contains substantially no plasticizer, which prevents impurities from being mixed into the PTFE. "Substantially free of plasticizer" means that the content of plasticizer relative to polypropylene is 1.0% by mass or less.

[0059] The surface roughness of the inner wall 2a is preferably 1.00 μm or less. This prevents fibrillation of PTFE due to contact with the inner wall 2a. The lower limit is not particularly limited, but is usually about 0.20 μm. The above surface roughness is calculated by observing the surface at a magnification of 5x using a Keyence VK-X1000 series shape analysis laser microscope to obtain an observed image, measuring the arithmetic mean roughness of the obtained image at a distance of 2.5 mm using the analysis application provided with the device, and similarly taking images of a total of three locations, measuring the arithmetic mean roughness, and calculating the average value of these values.

[0060] The container of the first disclosure is not limited to the above-mentioned form, and may be in other forms. For example, as shown in FIG. 4, the inner wall 2a and the outer wall 2b on the side surface may be reverse tapered. Also, as shown in FIG. 5, the inner wall 2a of the side surface may be forward tapered, and the outer wall 2b may be non-tapered (linear along the normal line). Also, as shown in Figure 6, the configuration may be the opposite of that shown in Figure 2, i.e., a protrusion 3b is provided on the part of the lid 3 that contacts the outer wall 2b on the inside, and a step-like difference 2e is provided on the outside of the opening 2c of the main body 2, and the lid 3 may be attached to the opening 2c with the protrusion 3b and the difference 2e meshing with each other.

[0061] A second aspect of the present disclosure is a container for filling with polytetrafluoroethylene, wherein the mass of the polytetrafluoroethylene filled is 10 kg or less.

[0062] In the second container of the present disclosure, the mass of PTFE filled is 10 kg or less, so that the force generated by its own weight is less likely to be applied to the PTFE powder, making it less likely to be compacted, thereby suppressing fibrillation. In addition, the container of the second disclosure is preferably filled with PTFE powder having a low apparent density, which makes it difficult for the force generated by its own weight to be applied to the PTFE powder, making it difficult for it to be compacted, thereby suppressing fibrillation.

[0063] In the container of the second disclosure, the mass of the PTFE to be filled is preferably 8 kg or less, more preferably 6 kg or less, and even more preferably 5 kg or less. The lower limit is not particularly limited, but is usually 1 kg or more.

[0064] The upper limit of the internal volume of the container of the second present disclosure is preferably 75 L or less, more preferably 60 L or less, even more preferably 50 L or less, and even more preferably 40 L or less. The lower limit is not particularly limited, but is preferably 5 L or more, and more preferably 10 L or more.

[0065] The container of the second disclosure may have a cylindrical side inner wall with a forward or reverse taper, or may have a cylindrical side inner wall with no tapering (straight line along the normal line). In terms of suppressing fibrillation, it is preferable that the inner wall of the side is a cylindrical side wall with a forward or reverse taper. Examples of containers having a cylindrical side inner wall with a forward or reverse taper include those having the same configuration as the container of the first disclosure (configurations shown in Figs. 1 to 6). Examples of containers having a cylindrical side inner wall with no tapering (straight line along the normal line) include those shown in Fig. 7.

[0066] Hereinafter, the first and second containers of the present disclosure will be collectively referred to as the containers of the present disclosure.

[0067] The container of the present disclosure may be filled with a moisture absorbent to maintain a dry state inside the container. Specific examples of the moisture absorbent include silica gel, calcium oxide, calcium chloride, etc., with silica gel and calcium oxide being preferred, and silica gel being more preferred. The moisture absorbent may be in the form of granules or sheets. It may be used in a packaging material or in a bare state. It may be placed on the PTFE filled in the container or in a location on the inner surface of the container, such as the back side of the lid.

[0068] When a conventional container is used, it is necessary to store the container at a low temperature (5 to 20°C) to suppress fibrillation, but in the container of the present disclosure, fibrillation is unlikely to occur even at room temperature. Therefore, depending on the region or time of year, PTFE can be stored without temperature control, which has the advantage of reducing the burden on the container during storage. The present disclosure also relates to a storage method for filling the container of the present disclosure with PTFE and storing the same. In the storage method of the present disclosure, PTFE can be stored at room temperature (15 to 30°C (preferably 25 to 30°C)).

[0069] The PTFE filled in the container of the present disclosure will be described below.

[0070] The above-mentioned PTFE can be suitably used as a binder for electrochemical devices. Examples of electrochemical devices include lithium ion secondary batteries, lithium ion capacitors, capacitors (hybrid capacitors, electric double layer capacitors), radical batteries, solar cells (particularly dye-sensitized solar cells), lithium ion primary batteries, fuel cells, various electrochemical sensors, electrochromic elements, electrochemical switching elements, aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc. The binder may be an electrode binder or a solid electrolyte binder.

[0071] When the above PTFE is used as a binder for electrochemical devices, the above PTFE may be used alone or in combination with other materials (for example, polymers other than PTFE).

[0072] The PTFE is preferably in the form of a powder.

[0073] Since the above-mentioned PTFE is useful as a binder for electrochemical devices such as batteries, is prone to fillerization, and the present disclosure is particularly effective therefor, it is preferable that the extrusion pressure at a reduction ratio (RR) of 100 is 5 MPa or more and / or that the PTFE is stretchable, and it is more preferable that the extrusion pressure at a RR of 100 is 5 MPa or more and the PTFE is stretchable.

[0074] The above-mentioned PTFE preferably has an extrusion pressure of 5 MPa or more at a reduction ratio (RR) of 100. From the viewpoint of improving the handleability, binding strength, and flexibility of the electrodes, etc., the extrusion pressure is more preferably 10 MPa or more, even more preferably 12 MPa or more, even more preferably 13 MPa or more, and particularly preferably 15 MPa or more. In terms of improving processability, the extrusion pressure in RR100 is preferably 50 MPa or less, more preferably 40 MPa or less, even more preferably 35 MPa or less, even more preferably 30 MPa or less, even more preferably 25 MPa or less, and particularly preferably 20 MPa or less.

[0075] In terms of improving the handling properties, binding strength, and flexibility of electrodes, etc., the above-mentioned PTFE preferably has an extrusion pressure of 10 Pa or more in RR300, more preferably 15 MPa or more, even more preferably 20 MPa or more, even more preferably 25 MPa or more, and particularly preferably 30 MPa or more. The extrusion pressure in RR300 is preferably 45 MPa or less, and more preferably 40 MPa or less, in terms of improving processability.

[0076] The extrusion pressure in RR100 is measured by the following method. 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name: Isopar E, ExxonMobil) as an extrusion aid are mixed in a polyethylene container for 3 minutes. At room temperature (25±2°C), the above mixture is filled into the cylinder of an extruder, and a load of 0.47 MPa is applied to the piston inserted in the cylinder and held for 1 minute. The mixture is then extruded from the orifice at a ram speed of 18 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice (reduction ratio) is 100. In the latter half of the extrusion operation, the load (N) when the pressure reaches equilibrium is divided by the cross-sectional area of ​​the cylinder to determine the extrusion pressure (MPa).

[0077] The extrusion pressure in RR300 is measured by the following method. 50 g of PTFE powder and 11.00 g of hydrocarbon oil (trade name: Isopar E, ExxonMobil) as an extrusion aid are mixed in a polyethylene container for 3 minutes. The mixture is filled into the cylinder of an extruder at room temperature (25±2°C), and a load of 0.47 MPa is applied to the piston inserted in the cylinder and held for 1 minute. The mixture is then extruded from the orifice at a ram speed of 18 mm / min. The ratio of the cross-sectional area of ​​the cylinder to the cross-sectional area of ​​the orifice (reduction ratio) is 300. In the latter half of the extrusion operation, the load (N) when the pressure reaches equilibrium is divided by the cross-sectional area of ​​the cylinder to determine the extrusion pressure (MPa).

[0078] The PTFE may be either stretchable or non-stretchable, but is preferably stretchable. Being stretchable means that a stretched body can be obtained in the following stretching test. The bead obtained by the above paste extrusion with RR100 is dried at 230°C for 30 minutes to remove the lubricant. The dried bead is cut to an appropriate length, placed in an oven heated to 300°C, and stretched in the oven at a stretching speed of 1000% / sec.

[0079] The PTFE is preferably stretchable up to 25 times in terms of improving the handling properties, binding strength, and flexibility of the electrode and the like. Whether or not the film can be stretched 25 times can be confirmed by the following stretching test. The bead obtained by the above paste extrusion at RR100 is dried at 230°C for 30 minutes to remove the lubricant. The dried bead is cut to an appropriate length and placed in an oven heated to 300°C. In the oven, it is stretched at a stretching speed of 1000% / sec until it becomes 25 times its length before the stretching test. If it does not break during stretching, it is judged that it can be stretched to 25 times.

[0080] It is preferable that the PTFE is substantially free of moisture. This allows a wide range of electrode active materials to be combined, which is advantageous in terms of the production process. "Substantially free of moisture" means that the moisture content of the PTFE is 0.050% by mass or less. The water content is preferably 0.040% by mass or less, more preferably 0.020% by mass or less, even more preferably 0.010% by mass or less, even more preferably 0.005% by mass or less, and particularly preferably 0.002% by mass or less. The water content is measured by the following method. The mass of the PTFE powder is measured before and after heating at 150°C for 2 hours, and calculated according to the following formula. Samples are taken three times, and the values ​​are calculated respectively, and the average value is calculated. Moisture content (mass%) = [(mass (g) of PTFE powder before heating) - (mass (g) of PTFE powder after heating)] / (mass (g) of PTFE powder before heating) x 100

[0081] From the viewpoint of improving the handleability, the PTFE has an apparent density of preferably 0.40 g / ml or more, more preferably 0.43 g / ml or more, even more preferably 0.45 g / ml or more, and even more preferably 0.48 g / ml or more. The upper limit is not particularly limited, but may be 0.60 g / ml. The apparent density is measured in accordance with JIS K 6892.

[0082] In terms of being able to suppress fibrillation, the above-mentioned PTFE preferably has an apparent density of less than 0.50 g / ml, more preferably 0.48 g / ml or less, even more preferably 0.45 g / ml or less, even more preferably 0.40 g / ml or less, particularly preferably less than 0.40 g / ml, and preferably 0.20 g / ml or more, more preferably 0.25 g / ml or more, even more preferably 0.30 g / ml or more, and particularly preferably 0.35 g / ml or more.

[0083] In terms of improving handleability, the above-mentioned PTFE has a powder particle size of preferably 300 μm or more, more preferably 450 μm or more, even more preferably 500 μm or more, even more preferably 550 μm or more, and particularly preferably 600 μm or more, and is preferably 1000 μm or less, more preferably 900 μm or less, even more preferably 800 μm or less, and particularly preferably 700 μm or less. The powder particle size is determined by a laser diffraction method. It is performed in a dry state using a HELOS&ROD OS system (product name, manufactured by SYMPATEC). The powder to be measured is dispersed with compressed air at a dispersion pressure of 2 bar, and the measurement sensor detects the shadow of the powder to be measured projected by a laser to calculate the particle size distribution of the powder to be measured, and the average particle size (50% cumulative particle size) d50 is calculated based on the volume.

[0084] In order to suppress fibrillation, the above-mentioned PTFE preferably has a powder particle size of less than 600 μm, more preferably 400 μm or less, even more preferably 300 μm or less, particularly preferably less than 300 μm, and preferably 10 μm or more, more preferably 50 μm or more, particularly preferably 100 μm or more.

[0085] In terms of improving handleability, extensibility, binding strength, and flexibility of electrodes, etc., the above-mentioned PTFE preferably has a standard specific gravity (SSG) of 2.200 or less, more preferably 2.180 or less, even more preferably 2.170 or less, even more preferably 2.160 or less, even more preferably 2.150 or less, and even more preferably 2.145 or less. The SSG is also preferably equal to or greater than 2.130. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.

[0086] The above-mentioned PTFE has a high molecular weight, and in view of improving the binding strength and the flexibility of the electrode, etc., the average primary particle size is preferably 350 nm or less, more preferably 330 nm or less, even more preferably 320 nm or less, even more preferably 300 nm or less, even more preferably 280 nm or less, particularly preferably 250 nm or less, and is preferably 100 nm or more, more preferably 150 nm or more, even more preferably 170 nm or more, and particularly preferably 200 nm or more. The average primary particle size is measured by the following method. The PTFE aqueous dispersion is diluted with water until the solid content is 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph are measured to create a calibration curve. Using this calibration curve, the number-average particle diameter is determined from the measured transmittance of the 550 nm projected light of each sample, and is taken as the average primary particle diameter.

[0087] From the viewpoint of excellent handling properties, the PTFE may have an average aspect ratio of 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, even more preferably 1.6 or less, even more preferably 1.5 or less, even more preferably 1.4 or less, even more preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. The average aspect ratio may also be 1.0 or more. The above average aspect ratio is determined by observing PTFE powder or an aqueous PTFE dispersion diluted to a solid content of approximately 1% by mass with a scanning electron microscope (SEM), processing the images of 200 or more particles randomly selected, and averaging the ratio of the long axis to the short axis.

[0088] The PTFE preferably has non-melt secondary processability, which means that the melt flow rate cannot be measured at a temperature higher than the melting point in accordance with ASTM D-1238 and D-2116, in other words, that the PTFE does not flow easily even in the melting temperature range.

[0089] The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0 mass% or more of TFE units and 1.0 mass% or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units. As the PTFE, the modified PTFE is preferable in terms of improving the binding strength and flexibility of the electrode, etc. A TFE homopolymer is preferable in terms of improving the handling property.

[0090] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in terms of improving stretchability, binding strength, and flexibility of electrodes, etc. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and particularly preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, even more preferably 0.20% by mass, even more preferably 0.15% by mass, even more preferably 0.10% by mass, even more preferably 0.08% by mass, even more preferably 0.05% by mass, and most preferably 0.03% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0091] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0092] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene, perfluorovinyl ether, perfluoroallyl ether, (perfluoroalkyl)ethylene, ethylene, etc. The modified monomer used may be one type or multiple types.

[0093] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORf (A) (wherein Rf represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0094] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rf in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0095] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0096] The perfluorovinyl ether further includes those in which Rf in the above general formula (A) is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rf is the following formula:

[0097] [ka]

[0098] (wherein m represents 0 or an integer of 1 to 4), Rf is a group represented by the following formula:

[0099] [ka]

[0100] (wherein n represents an integer of 1 to 4).

[0101] The (perfluoroalkyl)ethylene (PFAE) is not particularly limited, and examples thereof include (perfluorobutyl)ethylene (PFBE) and (perfluorohexyl)ethylene.

[0102] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORf 1 (B) (In the formula, Rf 1 represents a perfluoro organic group.

[0103] Above Rf 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.

[0104] As the above-mentioned modified monomer, from the viewpoint of improving the extensibility, binding strength, and flexibility of the electrode, etc., at least one selected from the group consisting of PAVE and HFP is preferable, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) (PMVE) and HFP is more preferable.

[0105] As the other modified monomer, at least one selected from the group consisting of VDF, HFP, CTFE and PAVE is preferable, and at least one selected from the group consisting of VDF, HFP and CTFE is more preferable, in that a composite sheet having excellent strength can be formed. From the viewpoint of improving heat resistance, one preferred embodiment is that the PTFE contains TFE units, VDF units and HFP units, and the total amount of the VDF units and the HFP units is 1.0 mass % or less based on the total polymerized units.

[0106] The PTFE preferably has a core-shell structure in terms of ease of handling. An example of the PTFE having a core-shell structure is modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. An example of such modified PTFE is the PTFE described in JP-A-2005-527652.

[0107] In terms of being able to form a composite sheet having excellent strength, the PTFE preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on a fluororesin that has not been heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.

[0108] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.

[0109] The PTFE has a number average molecular weight (Mn) of 3.0×10 and is preferred because it can form a composite sheet with excellent strength. 6 More preferably, it is 3.2×10 6More preferably, it is 3.5×10 or more. 6 More preferably, it is 3.7×10 or more. 6 More preferably, it is 4.0×10 or more. 6 It is particularly preferable that the number average molecular weight is 7.0×10 or more. 6 Preferably, it is 6.5×10 or less. 6 More preferably, it is 6.0×10 or less. 6 More preferably, it is 5.5×10 or less. 6 Even more preferably, it is 5.0×10 or less. 6 It is particularly preferred that: The number average molecular weight is a molecular weight calculated from the heat of crystallization estimated by measuring the temperature drop of a melted fluororesin using a differential scanning calorimeter (DSC) according to the method described in the following document. The measurement is carried out five times, and the average value of the three values ​​excluding the maximum and minimum values ​​is used. Literature: Suwa, T.; Takehisa, M.; Machi, S., J. Appl. Polym. Sci. vol. 17, pp. 3253 (1973).

[0110] The PTFE is preferably substantially free of fluorine-containing compounds having a molecular weight of not more than 1000. "Substantially free of fluorine-containing compounds" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is more preferably less than 25 mass ppb, even more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, even more preferably 3 mass ppb or less, and particularly preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0111] The amount of the fluorine-containing compound having a molecular weight of 1,000 or less is measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The resulting extract is concentrated using nitrogen purging as appropriate, and the fluorine-containing compounds in the concentrated extract are measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate fluorine-containing compound is confirmed. Prepare aqueous solutions with five or more levels of content of the standard substance, perform LC / MS analysis of the aqueous solutions with each content, plot the relationship between the content and the area for that content, and draw a calibration curve. Using the above calibration curve, the area of ​​the LC / MS chromatogram of the fluorine-containing compounds in the extract is converted to the content of the fluorine-containing compounds. The lower detection limit in this measurement method is 10 ppb by mass.

[0112] The amount of the fluorine-containing compound having a molecular weight of 1000 or less can also be measured by the following method. Weigh out 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment at 60°C for 2 hours. After standing at room temperature, remove the solids to obtain an extract. The resulting extract is appropriately concentrated with nitrogen purging, and the fluorine-containing compounds in the concentrated extract are measured by LC / MS / MS. Molecular weight information is extracted from the obtained LC / MS spectrum, and a match with the structural formula of the candidate fluorine-containing compound is confirmed. Five levels of methanol standard solutions of fluorine-containing compounds with known concentrations are prepared, and measurements are performed using a liquid chromatograph mass spectrometer. A calibration curve is created using a first-order approximation from the methanol standard solution concentration and the peak integral value in each concentration range. The content of the fluorine-containing compound in the extract is measured from the above calibration curve, and the content of the fluorine-containing compound in the sample is converted. The detection limit in this measurement method is 1 ppb by mass.

[0113] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include a fluorine-containing compound having a hydrophilic group and a molecular weight of 1000 g / mol or less. The molecular weight of the fluorine-containing compound is preferably 800 or less, and more preferably 500 or less. Polymer particles obtained by polymerization in the presence of a fluorine-containing surfactant usually contain a fluorine-containing surfactant in addition to PTFE. In this specification, the fluorine-containing surfactant is one that is used during polymerization. The above-mentioned fluorine-containing compound having a molecular weight of 1000 or less may be a compound that is not added during polymerization, for example, a compound that is generated as a by-product during polymerization. In addition, when the fluorine-containing compound having a molecular weight of 1000 or less contains an anionic moiety and a cationic moiety, it means a compound containing fluorine in which the molecular weight of the anionic moiety is 1000 or less. The fluorine-containing compound having a molecular weight of 1000 or less does not include PTFE.

[0114] The hydrophilic group may be, for example, -COOM, -SO2M, or -SO3M, where -COOM, -SO3M (in each formula, M is H, a metal atom, NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 1 is H or an organic group.

[0115] As the fluorine-containing surfactant, a surfactant containing fluorine (anionic fluorine-containing surfactant) whose anionic moiety has a molecular weight of 1000 or less can also be used. The "anionic moiety" refers to the part of the fluorine-containing surfactant excluding the cation. For example, F(CF2) n1 In the case of COOM, "F(CF2) n1 The "COO" part. The anionic fluorine-containing surfactant may be a surfactant represented by the following general formula (N 0 ): X n0 -Rf n0 -Y 0 (N 0 ) (In the formula, X n0 is H, Cl or F. n0Y is a linear, branched or cyclic alkylene group having 3 to 20 carbon atoms, in which some or all of the H's are substituted with F, and the alkylene group may contain one or more ether bonds, and some of the H's may be substituted with Cl. 0 is an anionic group. Y 0 The anionic group may be -COOM, -SO2M, or -SO3M, and may be -COOM or -SO3M. M is H, a metal atom, or NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent, R 1 is H or an organic group. The metal atom includes alkali metals (Group 1), alkaline earth metals (Group 2), etc., such as Na, K, or Li. R 1 As the 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be: M is H, a metal atom or NR 1 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4, which may be H, Na, K, Li or NH4. Above Rf n0 may be one in which 50% or more of H is substituted with fluorine.

[0116] The above fluorine-containing surfactant may be one type of fluorine-containing surfactant, or a mixture containing two or more types of fluorine-containing surfactants.

[0117] Examples of the fluorine-containing surfactant include compounds represented by the following formula: The fluorine-containing surfactant may be a mixture of these compounds. F(CF2)7COOM, F(CF2)5COOM, H(CF2)6COOM, H(CF2)7COOM, CF3O(CF2)3OCHFCF2COOM, C3F7OCF(CF3)CF2OCF(CF3)COOM, CF3CF2CF2OCF(CF3)COOM, CF3CF2OCF2CF2OCF2COOM, C2F5OCF(CF3)CF2OCF(CF3)COOM, CF3OCF(CF3)CF2OCF(CF3)COOM, CF2ClCF2CF2OCF(CF3)CF2OCF2COOM, CF2ClCF2CF2OCF2CF(CF3)OCF2COOM, CF2ClCF(CF3)OCF(CF3)CF2OCF2COOM, CF2ClCF(CF3)OCF2CF(CF3)OCF2COOM, and [ka] (In each formula, M is H, metal atom, NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent. 1 is H or an organic group. It is preferable that the PTFE does not substantially contain any of the fluorine-containing compounds represented by the above formulas.

[0118] In each of the above formulas, M is H, a metal atom, or NR 1 4, H, an alkali metal (group 1), an alkaline earth metal (group 2) or NR 1 4, which may be H, Na, K, Li or NH4. R 1 is H or C 1-10 may be an organic group of H or C 1-4 may be an organic group of H or C 1-4 The alkyl group may be:

[0119] When the PTFE is substantially free of any of the fluorine-containing compounds represented by the above formulas, gas generation and deterioration of battery characteristics can be suppressed, and the sheet strength can also be improved. "Substantially free of any of the fluorine-containing compounds represented by the above formulas" means that the amount of the fluorine-containing compounds is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, even more preferably 3 mass ppb or less, and particularly preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0120] The PTFE has the following general formula: [C n-1 F 2n-1 COO - ]M + (In the formula, n is an integer of 9 to 14, preferably an integer of 9 to 12; M + represents a cation.) It is also preferable that the sheet is substantially free of a fluorine-containing compound represented by the formula (I). This makes it possible to suppress gas generation and deterioration of battery characteristics, and also to improve sheet strength. In the above formula, the cation M + The M in the above is the same as M described above. "Substantially free of the fluorine-containing compound represented by the above formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less relative to the PTFE. The amount of the fluorine-containing compound is preferably less than 25 mass ppb, more preferably 10 mass ppb or less, even more preferably 5 mass ppb or less, even more preferably 3 mass ppb or less, and particularly preferably 1 mass ppb or less. The lower limit is not particularly limited, and may be an amount below the detection limit.

[0121] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.

Example

[0122] Next, the present disclosure will be described with experimental examples, but the present disclosure is not limited to such examples only.

[0123] <Standard Specific Gravity (SSG)> Using a sample molded in accordance with ASTM D4895 89, it was measured by the water displacement method in accordance with ASTM D 792.

[0124] <RR100 Extrusion Pressure (Extrusion Pressure at Reduction Ratio 100)> 50 g of PTFE powder and 10.25 g of hydrocarbon oil (trade name: Isopar E, manufactured by ExxonMobil) as an extrusion aid were mixed in a polyethylene container for 3 minutes. At room temperature (25 ± 2°C), the above mixture was filled into the cylinder of an extruder, and a load of 0.47 MPa was applied to the piston inserted into the cylinder and held for 1 minute. Next, it was extruded from the orifice at a ram speed of 51 cm / min. The ratio of the cross-sectional area of the cylinder to the cross-sectional area of the orifice was 100. In the latter half of the extrusion operation, the value obtained by dividing the load (N) when the pressure reached an equilibrium state by the cross-sectional area of the cylinder was taken as the extrusion pressure (MPa).

[0125] <Elongation Test> The elongation test was carried out in accordance with the method described in JP-A-2002-201217 by the following method. The bead obtained by the above paste extrusion was heated at 230°C for 30 minutes to remove the lubricant from the bead. The bead (extrudate) was then cut to the appropriate length, clamped at each end with a clamp distance of 1.5 inches (38 mm) apart, and heated to 300°C in an air circulating oven. The clamps were then separated at a desired speed (stretch rate) until a separation distance corresponding to the desired stretch (total stretch) was achieved, and a stretch test (stretch test) was performed. The stretch method essentially followed the method disclosed in U.S. Pat. No. 4,576,869, except for the extrusion speed (51 cm / min instead of 84 cm / min). "Stretch" is the increase in length due to stretching, usually expressed as a percentage of the original length. In the stretch method, the stretch rate was 1000% / sec, and the total stretch was 2400%. In the above stretch test, those that did not break during stretching were considered stretchable, and those that broke during stretching were considered unstretchable.

[0126] <apparent density> Measurements were performed in accordance with JIS K6892.

[0127] <Powder particle size> The particle size was determined by the laser diffraction method. It was performed in a dry state using a HELOS&ROD OS system (product name, manufactured by SYMPATEC). The powder to be measured was dispersed with compressed air at a dispersion pressure of 2 bar, and the shadow of the powder to be measured projected by a laser was detected by the measurement sensor unit, and the particle size distribution of the powder to be measured was calculated, and the average particle size (50% cumulative particle size) d50 was determined on a volume basis. The powder particle size was set to be equal to the particle size corresponding to 50% of the cumulative particle size distribution.

[0128] <Moisture content> About 20 g of PTFE powder was heated at 150° C. for 2 hours, the mass was measured before and after, and the mass was calculated according to the following formula. A sample was taken three times, and the mass was calculated for each time, and the average value was calculated. Moisture content (mass%) = [(mass (g) of PTFE powder before heating) - (mass (g) of PTFE powder after heating)] / (mass (g) of PTFE powder before heating) x 100

[0129] <Powder clumping property> 60 g of the stored PTFE powder was taken out from the container and sieved through a mesh (openings 1.54 mm), and the mass of the lumps remaining on the sieve was measured. The above procedure was repeated 10 times, and the average mass of the lumps remaining on the sieve was calculated. The powder's clumping tendency was evaluated based on the calculated average mass (g) / 60 (g) x 100 (mass%). The smaller the value, the less likely the powder is to clump, and the better the result.

[0130] <Preparation of Positive Electrode Mixture> Li(Ni 0.6 Mn 0.2 Co 0.2 )O2 (NMC622), carbon black as a conductive additive, and PTFE powder as a binder were weighed out so that the mass ratio of the positive electrode active material: binder: conductive additive was 95: 2: 3. These materials were put into a blender (Osaka Chemical: WB-1) and stirred at 25,000 rpm for 60 seconds to obtain a positive electrode mixture.

[0131] <Ease of binding> A sieve with a mesh size of 2.0 mm, a sieve with a mesh size of 0.15 mm, and a bottom receiving container were stacked vertically on a shaker, and the positive electrode mixture mixture was placed on the top sieve. After operating at a speed of 50 rpm for 1 minute, the mass of the mixture sieved into the bottom receiving container was measured. The adhesion property of the mixture (ease of the mixture to be held together) was evaluated based on the desorption rate calculated from the following formula. Desorption rate = (W2 / W1) x 100 (%) (Wherein, W1 is the total mass (g) of the mixture before the test, and W2 is the mass (g) of the screened mixture.) Excellent: Detachment rate less than 1% Good: Detachment rate is 1% or more but less than 2% Acceptable: Detachment rate is 2% or more but less than 3% Defective: Detachment rate 3% or more

[0132] Experimental Example 1 15 kg of PTFE powder was placed in a 60 L plastic container (material: polypropylene, no plasticizer (content relative to polypropylene: 0% by mass), surface roughness of the inner wall: 0.23 μm) with a forward taper angle of 3.0° and a difference between the upper and lower inner diameters of 30 mm, and stored for half a year in an atmosphere at 25°C. The clumping tendency of the stored PTFE powder was 0.4% by mass and the moisture content was 0.002% by mass. A positive electrode mixture was prepared by the above-mentioned method, and the ease of bonding was evaluated. The detachment rate was 0.4 mass%, and the ease of bonding was excellent. The PTFE powder used was the PTFE powder described in Example 1 of WO 2023 / 054709, and had a standard specific gravity (SSG) of 2.159, an RR100 extrusion pressure of 15.1 MPa, extensibility, a powder particle size of 540 μm, an apparent density of 0.48 g / ml, and a moisture content of 0.002% by mass.

[0133] Experimental Example 2 The container has a lid attached to the opening and a clamp to fix the container, and has the same shape as in Experimental Example 1. The PTFE powder filled in the container is the PTFE powder described in Example 2 of International Publication No. 2023 / 054707, and has a standard specific gravity (SSG) of 2.145, RR100 extrusion pressure of 17.4 MPa, stretchable, powder particle size of 540 μm, apparent density of 0.43 g / ml, and moisture content of 0.000% by mass. It was stored for half a year in an atmosphere at 25 ° C. in the same manner as in Experimental Example 1. The clumping property of the stored PTFE powder was 0.3% by mass and the moisture content was 0.001% by mass. The adhesiveness of the positive electrode mixture was evaluated, and the detachment rate was 0.5 mass %, indicating that the adhesiveness was excellent.

[0134] Experimental Example 3 The container was stored for half a year in an atmosphere at 10°C in the same manner as in Experimental Example 2, except that the step on the lid and the protrusion on the container body were interlocked and silica gel was used as a moisture absorbent for the container. The clumping tendency of the stored PTFE powder was 0.2% by mass, and the moisture content was 0.000% by mass. The adhesiveness of the positive electrode mixture was evaluated, and the detachment rate was 0.5% by mass, indicating that the adhesiveness was excellent.

[0135] Experimental Example 4 The PTFE powder to be filled in the container is the PTFE powder described in Example 18 of International Publication No. 2023 / 054723, and was stored for half a year in an atmosphere at 25 ° C. in the same manner as in Experimental Example 2, except that the standard specific gravity (SSG) was 2.170, the RR100 extrusion pressure was 5.6 MPa, it was not stretchable, the powder particle size was 540 μm, the apparent density was 0.48 g / ml, and the moisture content was 0.001 mass%. The clumping property of the stored PTFE powder was 0.1 mass%, and the moisture content was 0.002 mass%. As a result of evaluating the ease of binding of the positive electrode mixture, the detachment rate was 0.8 mass%, and the ease of binding was excellent.

[0136] Experimental Example 5 The container was stored for half a year in an atmosphere at 25°C in the same manner as in Experimental Example 1, except that 5 kg of PTFE powder was placed in a 30 L plastic container (material: polypropylene, no plasticizer (content relative to polypropylene: 0% by mass), surface roughness of the inner wall: 0.23 μm) with a forward taper angle of 0° and a difference between the upper inner diameter and the lower inner diameter of 0 mm. The clumping tendency of the stored PTFE powder was 2.5% by mass, and the moisture content was 0.005% by mass. The adhesiveness of the positive electrode mixture was evaluated, and the adhesiveness was fair, with a detachment rate of 2.1% by mass.

[0137] Experimental Example 6 The PTFE aqueous dispersion obtained by Production Example 1 of WO 2023 / 054713 was diluted to a solid content concentration of 8.5% by mass, the liquid temperature was adjusted to 10 ° C, nitric acid was added, and high-speed stirring was performed in a container to cause coagulation, and the mixture was dried at 210 ° C to obtain a PTFE powder. The obtained PTFE powder had a standard specific gravity (SSG) of 2.158, an RR100 extrusion pressure of 16.3 MPa, was stretchable, had a powder particle size of 145 μm, an apparent density of 0.35 g / ml, and a moisture content of 0.002 mass%. The obtained PTFE powder was stored for half a year in an atmosphere at 25 ° C. in the same manner as in Experimental Example 5. The clumping property of the stored PTFE powder was 1.5 mass%, and the moisture content was 0.005 mass%. As a result of evaluating the ease of binding of the positive electrode mixture, the detachment rate was 1.3 mass%, and the ease of binding was good.

[0138] Experimental Example 7 A plastic container (material: polypropylene, no plasticizer (content relative to polypropylene: 0% by mass), surface roughness of the inner wall: 0.23 μm) with a taper angle of 0°, i.e., a difference between the upper inner diameter and the lower inner diameter of 0 mm was used and stored in the same manner as in Experimental Example 1. The clumping property of the stored PTFE powder was 5.6% by mass. A positive electrode mixture was prepared using the above method, and the ease of bonding was evaluated. The detachment rate was 3.6 mass %, and the ease of bonding was poor. [Explanation of symbols]

[0139] 1: Container 2: Main unit 2a:Inner wall 2b: Exterior wall 2c: opening 2d: Protrusion 2e: Step 3: Lid 3a: step 3b: Protrusion 4: Clamp 4a: Mounting part A: Taper angle

Claims

1. A container for filling polytetrafluoroethylene, comprising: A container whose inner side wall is cylindrical and tapered either forward or reverse.

2. 2. The container according to claim 1, wherein the polytetrafluoroethylene has an extrusion pressure of 5 MPa or more at a reduction ratio of 100 and / or is stretchable.

3. 3. The container according to claim 1, wherein the polytetrafluoroethylene has an extrusion pressure of 5 MPa or more at a reduction ratio of 100 and is stretchable.

4. 3. The container according to claim 1, wherein the polytetrafluoroethylene has an extrusion pressure of 5 to 20 MPa at a reduction ratio of 100.

5. 3. The container according to claim 1, wherein the polytetrafluoroethylene is used as a binder for an electrochemical device.

6. 3. The container according to claim 1, wherein the difference between the inner diameter of the upper surface and the inner diameter of the lower surface is 5 to 100 mm.

7. 3. The container according to claim 1, wherein the taper angle is 0.5 to 10°.

8. 3. The container according to claim 1 or 2, wherein the material is polypropylene substantially free of plasticizer.

9. 3. The container according to claim 1, wherein the surface roughness of the inner wall is 1.00 μm or less.

10. A body having an opening; A lid attached to the opening; 3. The container according to claim 1 or 2, further comprising a clamp for fixing the lid.

11. The container of claim 10, wherein the lid is attached to the opening with a step on the lid engaging with a protrusion on the main body and / or with a protrusion on the lid engaging with a step on the main body.

12. 3. The container according to claim 1, wherein the polytetrafluoroethylene has a moisture content of 0.050% by mass or less.

13. 3. The container according to claim 1, wherein the apparent density of the polytetrafluoroethylene is 0.40 to 0.60 g / ml.

14. 3. The container according to claim 1, wherein the apparent density of the polytetrafluoroethylene is 0.43 to 0.60 g / ml.

15. 3. The container according to claim 1, wherein the powder particle size of the polytetrafluoroethylene is 300 to 700 μm.

16. 3. The container according to claim 1, wherein the powder particle size of the polytetrafluoroethylene is 500 to 700 μm.

17. 3. The container according to claim 1, wherein the standard specific gravity of said polytetrafluoroethylene is 2.200 or less.

18. 3. The container according to claim 1, wherein the standard specific gravity of the polytetrafluoroethylene is 2.130 to 2.

170.

19. 3. The container according to claim 1, wherein the polytetrafluoroethylene has an apparent density of 0.43 to 0.60 g / ml, a powder particle size of 500 to 700 μm, and a standard specific gravity of 2.130 to 2.

170.

20. 3. The container according to claim 1, wherein the polytetrafluoroethylene is a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing polymerization units based on tetrafluoroethylene and polymerization units based on a modified monomer.

21. 21. The container according to claim 20, wherein the modifying monomer is at least one selected from the group consisting of perfluoro(methyl vinyl ether) and hexafluoropropylene.

22. 3. The container according to claim 1 or 2, which is filled with polytetrafluoroethylene.

23. 3. The container according to claim 1 or 2, wherein the container comprises a moisture absorbent.

24. 3. A method for storing polytetrafluoroethylene, comprising filling the container according to claim 1 or 2 with the polytetrafluoroethylene and storing the same.

25. A container for filling polytetrafluoroethylene, comprising: A container in which the mass of the polytetrafluoroethylene filled therein is 10 kg or less.

26. 26. The container according to claim 25, wherein the mass of the polytetrafluoroethylene to be filled is 5 kg or less.

27. 27. The container according to claim 25 or 26, wherein the powder particle size of the polytetrafluoroethylene is 100 μm or more and less than 600 μm.

28. 27. The container according to claim 25 or 26, wherein the apparent density of the polytetrafluoroethylene is 0.35 to 0.48 g / ml.

29. 27. The container according to claim 25 or 26, wherein the polytetrafluoroethylene has a moisture content of 0.050% by mass or less.

30. 27. The container according to claim 25 or 26, wherein the polytetrafluoroethylene has a moisture content of 0.005% by mass or less.

31. 27. The container according to claim 25 or 26, wherein the standard specific gravity of the polytetrafluoroethylene is 2.130 to 2.

170.

32. The container according to claim 25 or 26, wherein the polytetrafluoroethylene has a moisture content of 0.005% by mass or less, an apparent density of 0.35 to 0.48 g / ml, a powder particle size of 100 μm or more and less than 600 μm, and a standard specific gravity of 2.130 to 2.

170.

33. 27. The container according to claim 25 or 26, wherein the polytetrafluoroethylene has a powder particle size of 100 μm or more and less than 300 μm and / or an apparent density of 0.35 g / ml or more and less than 0.40 g / ml.

34. 27. The container according to claim 25 or 26, which is filled with polytetrafluoroethylene.

Citation Information

Patent Citations

  • a container with a body and a lid

    JP2003522683A

  • Container

    JP2004182299A

  • Shielded drum for transporting powdered chemicals

    JP2016511201A

  • Large diameter clampless, highly airtight plastic tank

    JP3234857U

  • Dispersion containing tetrafluoroethylene copolymer particle and its production

    JP1999343317A